The Effect of Budget Participation and Accountability Accounting on Managerial Performance at the Provincial Regional Development Planning Agency Southeast Sulawesi - Arvindi; Husin; Fitriaman (Escalate : Economics and Business Journal, 2026)
This study aims to determine the influence of budget participation and accountability accounting on managerial performance at the Regional Development Planning Agency of Southeast Sulawesi Province. The sample of this study amounted to 50 employees who were selected using purposive sampling techniques. The data collection method uses a questionnaire, with the measurement scale used being the Likert scale. The data analysis method used multiple linear regression analysis with the help of SPSS version 22 application. The results of this study show that (1) Budget participation has a positive and significant effect on managerial performance; (2) Accountability accounting has a positive and significant effect on managerial performance; (3) Budget participation and accountability accounting have a positive and significant effect on managerial performance.